Postcard from Georg Bredig to Max Bredig, February 15, 1938 - Bredig, Georg (1938)
Georg Bredig (1868-1944) advises his son, Max Bredig (1902-1977), to follow up with the situation regarding Alfred (1900-1944) and Eva Schnell (1913-1944). He also updates Max on freight shipments and tells him about a previous letter Max's sister, Marianne Homburger (1903-1986) wrote.
Keywords: Bredig, Georg, 1868-1944; Bredig, Max Albert, 1902-1977; Third Reich; Homburger, Marianne, 1903-1986; Schnell, Eva, 1913-1944; Schnell, Alfred, 1900-1944